A Systematic Review of Picosecond Laser in Dermatology: Evidence and Recommendations. Issue 1 (13th April 2020) - Wu, Douglas C.; Goldman, Mitchel P.; Wat, Heidi; Chan, Henry H.L.
Abstract : Background and Objectives: The use of picosecond laser in dermatology was originally focused on optimizing the removal of unwanted tattoos. Subsequent advances in this technology have broadened its clinical indications to include treatment of benign pigmented lesions, photodamage, melasma, and scar revision. In this systematic review, evidence‐based recommendations are developed for the use of picosecond laser in dermatology. Study Design/Materials and Methods: A comprehensive search of the English language literature was performed up to and including November 2019. Relevant citations were individually evaluated, synthesized, and categorized based on the Level of Evidence. With the addition of the authors' combined clinical experience, clinical recommendations were developed. Results: After application of inclusion and exclusion criteria, a total of 77 unique studies were evaluated. Treatment of benign pigmented lesions was associated with level I–IV evidence; rejuvenation was associated with level II evidence; melasma was associated with level II evidence; scar revision was associated with level II–III evidence; tattoo removal was associated with level I evidence. Conclusion: Picosecond laser is a safe and effective treatment modality for an increasing range of dermatologic indications. Further development of this technology is warranted. Lasers Surg. Med. © 2020 Wiley Periodicals, Inc.